Kajian pustaka asesmen status kondisi ekosistem mangrove - Gathot Winarso; Muhammad Kamal; Mohammad Syamsu Rosid; Wikanti Asriningrum; Jatna Supriatna (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
The mangrove area of the world has been decreasing and Indonesia has lost 1.6 million ha of mangrove during the period 1980-2005. In 2015 the status of Indonesia's mangroves was 3.5 million ha with 48% in good condition and 52% in degraded conditions. Therefore, mangrove forests should be conserved properly and utilized sustainably. Assessment of the status of mangrove conditions is essential in conservation planning and management so that it can be done better. However, the method for assessing the condition of mangrove forests is still diverse and has not been standardized, so a literature review and review of how to assess the condition of mangrove ecosystems from various literature needs to be done. The results of the study of various literatures, in general there are two types of assessments. The first assessment used canopy density indicators, tree density, structure and composition of vegetation including diversity index and environmental parameters which are used singly or a combination of some or all parameters and some that be correlated with ecological integrity. For the second assessment, using a comparison between the existing mangrove forest and the potential area to be overgrown with mangroves. There is a difference when assessing the potential area, there is the opinion of the area potentially seen by the status of the area whether or not the forest area, from the landsystem, the level of abrasion, pond area and the comparison of the coastline length overgrown with mangrove with a total coastline length. Both assessments with each indicator can be used in accordance with the objectives of the assessment of the condition.